Heat-shrinkable polyester film
By designing a specific polyester structure in the heat shrinkable film and controlling the amount of the modified alcohol mixture, the problems of adhesion and dimensional instability of the heat shrinkable film during the formation of sleeve-like labels are solved, achieving stable mechanical strength and stable production. Effect.
Patent Information
- Application Number
- CN202311745438.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-07-21
- Filing Date
- 2023-12-19
- Publication Date
- 2025-01-21
AI Technical Summary
During the process of forming a sleeve-like label, the existing heat shrink film is prone to bonding the inner and outer surfaces due to penetration of the palm-coated agent, which is difficult to unfold or spread. After storage, the mechanical strength changes greatly and the dimensions are unstable, resulting in production fractures and production capacity reduction.
By designing the dicarboxyl component and glycol component of the polyester film, including terephthalic acid, dimethyl terephthalate, ethylene glycol and a modified alcohol mixture, the amount of the modified alcohol mixture is controlled from 18 mol% to 26 mol % to ensure that the heat-shrinkable polyester film can stably withstand external tension and maintain dimensional stability under high production speeds.
The heat-shrinkable polyester film is less likely to have internal and external surface adhesion, has stable mechanical strength, and remains unchanged in size during storage and use, ensuring the stability of the production process and maintenance of production capacity.
Smart Images

Figure BDA0004614230360000091 
Figure BDA0004614230360000101 
Figure BDA0004614230360000102
Abstract
Description
Technical Field
[0001] The invention relates to a polyester film, in particular to a heat shrinkable polyester film. Background Art
[0002] PCT International Application Publication No. WO2022072477 discloses a heat shrinkable film. The heat shrinkable film comprises a copolyester, and the copolyester is formed by a polymerization reaction of a raw material composition. The raw material composition comprises a diacid component and a diol component. The diacid component comprises at least one of terephthalic acid and dimethyl terephthalate. The diol component comprises ethylene glycol, 2-methyl-1,3-propanediol, diethylene glycol and at least one other diol. The other diol is neopentyl glycol or 1,4-cyclohexanedimethanol. Through the design of the copolyester, the heat shrinkable film has a low shrinkage starting temperature, so when the heat shrinkable film is used as a sleeve-shaped label on the outer surface of a container, it can be carried out under low energy consumption conditions.
[0003] Generally speaking, the process of forming a sleeve-shaped label from a heat shrink film is to bond the heat shrink film through a bonding machine. The bonding machine overlaps the two ends of the heat shrink film in the vertical mechanical direction, and at the same time, a bonding agent is applied between the two ends to bond the two ends to form a hollow flat long film. Then, the hollow flat long film is cut into sections of hollow cut pieces of appropriate size, and then the hollow cut pieces are stretched open from the hollow part to form a sleeve. Then, the sleeve is heat-shrunk and wrapped on the container. Usually, when it is not necessary to make a sleeve immediately, the hollow flat long film will be wound into a cylindrical roll film for storage and standby. When it is made into a sleeve, the cylindrical roll film is unfolded into the hollow flat long film.
[0004] However, in the process of forming a sleeve-shaped label from the heat shrinkable film disclosed in the PCT international application, the sealing agent often penetrates from the two ends into the inner surface or outer surface of the hollow flat long film, causing the inner surface or outer surface to stick together when the hollow flat long film is rolled into a cylindrical roll film, making it difficult for the cylindrical roll film to unfold into the hollow flat long film or to expand from the hollow part of the hollow cut product, resulting in the problem of difficulty in producing the sleeve. In addition, although the PCT international application publication discloses that the elongation of the heat shrinkable film before and after storage for a period of time is greater than 200%, it is found through experiments (as shown in Comparative Example 5 of the experimental design of the present invention described below) that the difference between the elongation of the heat shrinkable film before and after storage for a period of time is large. Therefore, during the process of forming the hollow flat long film or the process of wrapping the sleeve in the container by heat shrinkage, the heat shrinkable film or the sleeve is easily broken at a high production speed of 300m / min to 500m / min due to external tension, resulting in production suspension and a problem of reduced production capacity per unit time. In addition, it is found through experiments that the heat shrinkable film will have a large degree of natural shrinkage after being stored for a period of time, resulting in the problem of unstable storage size of the heat shrinkable film, which cannot meet market demand.
[0005] In addition to the above-mentioned PCT international application publication, U.S. Patent Publication No. 7008698 and U.S. Patent Publication No. 20080057237 disclose that the shrink film formed by using 2-methyl-1,3-propanediol has excellent shrinkage. However, it is found through experiments that the shrink film formed by using 2-methyl-1,3-propanediol will cause a large change in mechanical strength (such as elongation) before and after storage and a large degree of natural shrinkage will occur if too much 2-methyl-1,3-propanediol is added, resulting in the problem of unstable storage dimensions of the heat shrink film. Under such circumstances, the shrink film of the above-mentioned patent case has properties that are not acceptable to the existing market.
[0006] Taiwan Invention Patent Publication No. TWI500654 discloses that the use of 10 mol% to 80 mol% of 1,4-cyclohexanedimethanol and 0.1 mol% to 50 mol% of 2-methyl-1,3-propanediol can reduce the shrinkage stress of the heat shrinkable film to avoid deformation of the container when the container is heat-shrinked or whitening during heat shrinkage and improve the problem of poor low-temperature shrinkage. However, it does not mention that adding excessive glycol will cause the heat shrinkable film to have unstable storage dimensions after being stored for a period of time.
[0007] Korean Patent Application Publication No. 20040051808 discloses that the shrink film formed by using 3 mol% to 45 mol% of 2-methyl-1,3-propanediol has certain shrinkage performance. Further, it is mentioned that when the amount of 2-methyl-1,3-propanediol is less than 3 mol%, the shoulder of the bottle will become loose due to shrinkage and sterilization treatment, and when it is greater than 45 mol%, the heat shrinkage speed is too fast, and problems such as end folding, shrinkage spots, wrinkles and deformation after shrinkage will occur. However, the patent application does not mention how to improve the large changes in mechanical strength (such as elongation) and dimensional instability after storage over time.
[0008] PCT International Application Publication No. WO2022076763A1 discloses that a shrinkable polyester film comprises a polyester, and the polyester is formed by reacting a diacid component and a diol component. The diol component includes ethylene glycol, 2-methyl-1,3-propanediol, 1,4-cyclohexanedimethanol and diethylene glycol. The shrinkable polyester film of the PCT International Application Publication has a shrinkage rate of greater than 60% in the perpendicular mechanical direction at 95°C and a shrinkage rate of less than 4% / °C at 65°C to 80°C. The shrinkable polyester film is used as a sleeve-shaped label on the outer surface of a container. The PCT international application publication focuses on controlling the shrinkage ratio and shrinkage rate to improve the fit with the container, so that containers with different requirements have good appearance after fitting. However, it does not mention the improvement methods for the large change in mechanical strength (such as elongation) before and after storage and the dimensional instability caused by inventory aging, and does not take into account the impact of the aging of the shrinkable polyester film on the shrinkable polyester film as a sleeve-shaped label. At the same time, this formula greatly affects the basic palm bonding requirements and cannot meet the requirements of commercially available shrinkable polyester films. Summary of the invention
[0009] The object of the present invention is to provide a heat-shrinkable polyester film.
[0010] The heat shrinkable polyester film of the present invention comprises polyester. The polyester is formed by a dicarboxyl component and a diol component. The dicarboxyl component comprises at least one of terephthalic acid or dimethyl terephthalate, and the diol component comprises ethylene glycol and a modified alcohol mixture. The modified alcohol mixture comprises a first modified alcohol and a second modified alcohol. The first modified alcohol is 2-methyl-1,3-propanediol, and the second modified alcohol is selected from neopentyl glycol, 1,4-cyclohexanedimethanol or a combination thereof. Based on the total amount of the diol component as 100 mol%, the total amount of the ethylene glycol is 74 mol% to 82 mol%, the total amount of the modified alcohol mixture is 18 mol% to 26 mol%, and the amount of the 2-methyl-1,3-propanediol is 3.5 mol% to 22 mol%. The heat-shrinkable polyester film satisfies the following (a) to (c): (a) after being immersed in hot water at 95°C for 10 seconds, the heat shrinkage in the direction perpendicular to the machine is greater than 48%; (b) after being immersed in hot water at 95°C for 10 seconds, the heat shrinkage in the machine direction is less than 5%; and (c) has an intrinsic viscosity greater than 0.50 dL / g.
[0011] In the heat-shrinkable polyester film of the present invention, the heat-shrinkable polyester film has a natural shrinkage rate of no more than 1%, and the natural shrinkage rate is [(A0-A1) / A0]×100%, A0 and A1 respectively represent the length of the heat-shrinkable polyester film in one direction before and after treatment, and the treatment temperature is 40°C, the relative humidity is 65% and the time is 168 hours.
[0012] In the heat-shrinkable polyester film of the present invention, the heat-shrinkable polyester film has a break elongation variation of less than 100%, and the break elongation variation is the absolute value of the difference between the break elongation of the heat-shrinkable polyester film before and after aging treatment, and the aging treatment temperature is 60° C. and the time is 1 hour.
[0013] In the heat-shrinkable polyester film of the present invention, the heat-shrinkable polyester film has a yield strength of 7.5 MPa to 13 MPa in a perpendicular machine direction.
[0014] In the heat-shrinkable polyester film of the present invention, based on 100 mol % of the total amount of the diol component, the total amount of the second modified alcohol is 4 mol % to 22 mol %.
[0015] In the heat-shrinkable polyester film of the present invention, based on 100 mol % of the total amount of the diol component, the total amount of the second modified alcohol is 4 mol % to 17 mol %.
[0016] In the heat-shrinkable polyester film of the present invention, based on 100 mol % of the total amount of the diol component, the amount of the 2-methyl-1,3-propanediol is 3.5 mol % to 20 mol %.
[0017] In the heat-shrinkable polyester film of the present invention, based on 100 mol% of the total amount of the diol component, the total amount of the modified alcohol mixture is 21 mol% to 25 mol%, and the amount of the 2-methyl-1,3-propanediol is 17 mol% to 20 mol%.
[0018] In the heat-shrinkable polyester film of the present invention, the diol component further comprises bis(2-hydroxyethyl)terephthalate.
[0019] In the heat-shrinkable polyester film of the present invention, the diol component does not include polyglycol.
[0020] The beneficial effect of the present invention is that through the design of polyester, the heat shrinkable polyester film can have all the following advantages: first, during the process of the heat shrinkable polyester film being introduced into the palm-closing machine and forming a hollow flat long film, the palm-closing agent will not penetrate into the inner surface or outer surface of the hollow flat long film, so that the problem of the inner surface or the outer surface being adhered together is not likely to occur, so that the sleeve can be smoothly produced. Furthermore, the difference between the elongation of the heat shrinkable polyester film before and after being stored for a period of time is small. Therefore, during the process of forming the hollow flat long film or the sleeve being heat-shrinked and wrapped in the container after being stored for a period of time, the heat shrinkable polyester film or the sleeve can withstand the external tension at a high production speed without the problem of breaking, so that the production capacity can be maintained per unit time. In addition, the degree of natural shrinkage of the heat shrinkable polyester film after being stored for a period of time is small, and it has excellent storage dimensional stability. Therefore, even if the heat shrinkable polyester film is not used immediately after production, the heat shrinkable polyester film can still maintain a certain size and can meet the needs of the industry. At the same time, by controlling the amount of the modified alcohol mixture to 18 mol % to 26 mol %, the production cost can be greatly reduced or the required properties of the heat-shrinkable polyester film can be met, thereby meeting market demand and enabling mass production. DETAILED DESCRIPTION
[0021] The heat-shrinkable polyester film of the present invention comprises polyester. The polyester is formed by a polycondensation reaction of a dicarboxyl (-COO-) component and a diol component. The dicarboxyl component comprises at least one of terephthalic acid and dimethyl terephthalate, and the diol component comprises ethylene glycol and a modified alcohol mixture. The modified alcohol mixture comprises a first modified alcohol and a second modified alcohol. The first modified alcohol is 2-methyl-1,3-propanediol, and the second modified alcohol is selected from neopentyl glycol, 1,4-cyclohexanedimethanol or a combination thereof. Based on the total amount of the diol component as 100 mol%, the total amount of the ethylene glycol is 74 mol% to 82 mol%, the total amount of the modified alcohol mixture is 18 mol% to 26 mol%, and the amount of the 2-methyl-1,3-propanediol is 3.5 mol% to 22 mol%. The heat-shrinkable polyester film satisfies the following (a) to (c): (a) after being immersed in hot water at 95°C for 10 seconds, the heat shrinkage in the direction perpendicular to the machine is greater than 48%; (b) after being immersed in hot water at 95°C for 10 seconds, the heat shrinkage in the machine direction is less than 5%; and (c) has an intrinsic viscosity greater than 0.50 dL / g.
[0022] The present invention will be described in detail below.
[0023] [Heat-shrinkable polyester film]
[0024] In some embodiments of the present invention, the terephthalic acid may be recycled terephthalic acid. In some embodiments of the present invention, the dimethyl terephthalate may be recycled dimethyl terephthalate.
[0025] In some embodiments of the present invention, based on the total amount of the diol component as 100 mol%, the amount of the 2-methyl-1,3-propanediol is 3.5 mol% to 20 mol%. In some embodiments of the present invention, based on the total amount of the diol component as 100 mol%, the total amount of the second modified alcohol is 4 mol% to 22 mol%. In some embodiments of the present invention, based on the total amount of the diol component as 100 mol%, the total amount of the second modified alcohol is 4 mol% to 17 mol%. In some embodiments of the present invention, based on the total amount of the diol component as 100 mol%, the total amount of the modified alcohol mixture is 21 mol% to 25 mol%, and the amount of the 2-methyl-1,3-propanediol is 17 mol% to 20 mol%. In some embodiments of the present invention, the diol component further comprises bis(2-hydroxyethyl)terephthalate. In some embodiments of the present invention, the bis(2-hydroxyethyl)terephthalate may be recycled bis(2-hydroxyethyl)terephthalate.
[0026] It is worth noting that when the modified alcohol mixture is less than 18 mol%, the shrinkage of the heat-shrinkable polyester film is insufficient or it is difficult to close the palms, resulting in the heat-shrinkable polyester film being easily separated from each other by external forces in the subsequent process when the two ends of the bonded film are formed into a hollow flat long film, or even after being heat-shrinked and wrapped in a container. When the modified alcohol mixture is greater than 26 mol%, in addition to a significant increase in production costs, it may also be easy for the heat-shrinkable polyester film to penetrate on the palms, causing the heat-shrinkable polyester film to form a hollow flat long film. The palm-closing agent easily penetrates into the inner surface or outer surface of the hollow flat long film, causing the inner surface or outer surface to be easily bonded together, which is not conducive to the subsequent production of sleeves. At the same time, it may also happen that the heat-shrinkable polyester film will have a large degree of natural shrinkage after being stored for a period of time, causing the size of the heat-shrinkable polyester film to become smaller. Therefore, the heat-shrinkable polyester film has the problem of unstable storage size. In addition, some of them lead to insufficient mechanical strength of the heat-shrinkable polyester film, which cannot withstand external forces and breaks. As a result, the heat-shrinkable polyester film is easy to break under high production speed due to external tension during the process of forming the hollow flat long film or the process of the sleeve being heat-shrunk and wrapped in the container, thereby affecting production capacity. It can be seen that the content of the modified alcohol mixture has a great influence on the properties and applications of the heat-shrinkable polyester film.
[0027] In some embodiments of the present invention, after the heat shrinkable polyester film is immersed in hot water at 95°C for 10 seconds, the heat shrinkage rate in the perpendicular machine direction is 55% or more. In some embodiments of the present invention, after the heat shrinkable polyester film is immersed in hot water at 95°C for 10 seconds, the heat shrinkage rate in the perpendicular machine direction is 65% or more. In some embodiments of the present invention, after the heat shrinkable polyester film is immersed in hot water at 95°C for 10 seconds, the heat shrinkage rate in the machine direction is 4% or less.
[0028] In some embodiments of the present invention, the heat shrinkable polyester film has a natural shrinkage rate of no more than 1%, and the natural shrinkage rate is [(A0-A1) / A0]×100%, A0 and A1 respectively represent the length of the heat shrinkable polyester film in one direction before and after a treatment, and the treatment temperature is 40°C, the relative humidity is 65%, and the time is 168 hours. When the natural shrinkage rate is greater than 1%, it means that the heat shrinkable polyester film will have a large degree of natural shrinkage after being stored for a period of time, so that the size of the heat shrinkable polyester film becomes smaller. Therefore, the heat shrinkable polyester film has the problem of unstable storage size.
[0029] In some embodiments of the present invention, the heat shrinkable polyester film has a variation of elongation at break of less than 100%, and the variation of elongation at break is the absolute value of the difference between the elongation at break of the heat shrinkable polyester film before and after an aging treatment, and the aging treatment temperature is 60°C and the time is 1 hour. When the variation of elongation at break is greater than 100%, it means that the mechanical strength of the heat shrinkable polyester film is easily reduced and insufficient after being stored for a period of time, resulting in failure to withstand external force and fracture, so that the heat shrinkable polyester film is easy to break due to external tension at high production speed during the process of forming the hollow flat long film or the process of the sleeve being heat-shrunk and wrapped in the container.
[0030] In some embodiments of the present invention, the heat shrinkable polyester film has a yield strength of 7.5 MPa to 13 MPa in the perpendicular mechanical direction. When the yield strength in the perpendicular mechanical direction is greater than 13 MPa, the heat shrinkable polyester film is prone to insufficient strength on the palm, resulting in the heat shrinkable polyester film being easily separated from each other by the external force in the subsequent process during the process of forming the hollow flat long film, resulting in too low average peel strength and poor bonding stability. On the other hand, when the yield strength in the perpendicular mechanical direction is less than 7.5 MPa, the heat shrinkable polyester film is prone to penetration on the palm, resulting in the heat shrinkable polyester film being easily penetrated into the inner surface or outer surface of the hollow flat long film during the process of forming the hollow flat long film, resulting in the problem of the inner surface or outer surface being easily bonded together, which is not conducive to the subsequent production of the sleeve.
[0031] In some embodiments of the present invention, the thickness of the heat-shrinkable polyester film of the present invention ranges from 35 μm to 50 μm. In some embodiments of the present invention, the heat shrinkage rate of the heat-shrinkable polyester film in the perpendicular machine direction is 72% or more when placed in 95°C hot water for 10 seconds. In some embodiments of the present invention, the heat shrinkage rate of the heat-shrinkable polyester film in the machine direction is 3% or less when placed in 95°C hot water for 10 seconds.
[0032] In some embodiments of the present invention, the diol component does not include polyglycol [also known as polyethylene glycol, -O(CH2CH2O) n -, n is 2 or more]. In some embodiments of the present invention, the polyglycol is diethylene glycol or triethylene glycol. It is worth noting that, due to the presence of ethylene glycol during the reaction of the dicarboxyl component and the diol component, polyglycol is naturally produced, and the polyglycol also participates in the reaction. Therefore, even if the diol component of the present invention does not include polyglycol, the structure of the polyester of the present invention still includes polyglycol segments.
[0033] The polycondensation reaction includes a condensation reaction and a polymerization reaction. The condensation reaction is, for example, an esterification reaction or a transesterification reaction. In some embodiments of the present invention, the condensation reaction temperature is 220° C. to 270° C., and the time is 120 minutes to 480 minutes. In some embodiments of the present invention, the polymerization reaction temperature is 250° C. to 290° C., and the time is 120 minutes to 480 minutes.
[0034] [Method for preparing heat-shrinkable polyester film]
[0035] The method for preparing the heat-shrinkable polyester film of the present invention comprises the following steps: (a) forming a polyester component containing polyester into an unstretched sheet; and (b) subjecting the unstretched sheet to a preheating treatment, a stretching treatment and an annealing treatment in sequence.
[0036] The polyester is the polyester mentioned above, so it will not be described in detail.
[0037] The thickness of the unstretched plate can adopt the conventional thickness of the unstretched plate for forming the existing heat-shrinkable polyester film, or can be adjusted according to the requirements of the object to which the heat-shrinkable polyester film is applied. In some embodiments of the present invention, the unstretched plate is obtained by melting treatment and extrusion treatment. In some embodiments of the present invention, the unstretched plate is formed by a twin-axis screw device. In some embodiments of the present invention, the thickness of the unstretched plate ranges from 140μm to 240μm. In some embodiments of the present invention, the glass transition temperature of the unstretched plate ranges from 68°C to 77°C.
[0038] The purpose of the preheating treatment is to soften the unstretched plate so that the stretching treatment can be performed. The temperature of the preheating treatment is adjusted according to the material of the unstretched plate and the requirements of the stretching treatment. In some embodiments of the present invention, the preheating temperature range of the preheating treatment is from -20°C, the glass transition temperature of the unstretched plate, to +60°C, the glass transition temperature of the unstretched plate. The stretching treatment is performed along at least one stretching direction at a stretching temperature of from -40°C, the glass transition temperature of the unstretched plate, to +60°C, the glass transition temperature of the unstretched plate. The stretching direction is a mechanical direction or a perpendicular mechanical direction. In some embodiments of the present invention, the stretching treatment is performed at a stretching ratio of 4 to 6 times. In some embodiments of the present invention, the annealing temperature range of the annealing treatment is from -40°C, the glass transition temperature of the unstretched plate, to +60°C, the glass transition temperature of the unstretched plate.
[0039] The present invention will be further described with reference to the following examples, but it should be understood that the examples are only for illustration and should not be construed as limitations on the implementation of the present invention.
[0040] Example 1
[0041] A dicarboxyl component containing 100 mol% of terephthalic acid, a diol component containing 81 mol% of ethylene glycol and 19 mol% of a modified alcohol mixture, and 300 ppm (based on the total amount of ester particles) of tetraethylammonium hydroxide are mixed to form a mixture. The modified alcohol mixture includes 15 mol% of 2-methyl-1,3-propanediol (as the first modified alcohol) and 4 mol% of neopentyl glycol (as the second modified alcohol). The mixture is heated to 250°C, and an esterification reaction is carried out under a nitrogen environment. When the amount of water distilled reaches the theoretical value of the esterification reaction, 340 ppm (based on the total amount of ester particles) of ethylene glycol antimony (as a catalyst) and 15 ppm (based on the total amount of ester particles) of trimethyl phosphate (as a thermal stabilizer) are added, and a polymerization reaction is carried out under a vacuum environment of 275°C to obtain 35 kg of ester particles with an intrinsic viscosity (IV) greater than 0.52 dL / g.
[0042] The above-mentioned ester particles are dried until the moisture content is below 500ppm to obtain dried ester particles. The dried ester particles are introduced into a twin-screw extruder, and the dried ester particles are melt-treated in a multi-stage heating method. The temperature is raised from 210°C to 260°C. Next, a laminate comprising three polyester layers stacked from top to bottom is extruded from a die head device, and the thickness ratio of the three polyester layers is 1:8:1. Then, the laminate is cast to a cold drum device, and the laminate is cast through the cold drum device to obtain an unstretched plate with a thickness of 190μm and a glass transition temperature of 72°C.
[0043] The unstretched sheet was cut into cut pieces having a length of 12 cm in the perpendicular machine direction and a length of 30 cm in the machine direction, and then the cut pieces were passed through a transverse stretching machine (Bruckner; Model: Karo IV) for preheating, stretching and annealing to form a heat-shrinkable polyester film having a thickness of 40 μm. The preheating temperature of the preheating was 79° C., the stretching was performed under the conditions of a stretching temperature of 71° C. and stretching in a perpendicular machine direction with a stretching ratio of 4.8 and a stretching rate of 34% / sec, and the annealing temperature of the annealing was 56° C.
[0044] Examples 2 to 8 and Comparative Examples 1 to 15
[0045] The preparation methods of the heat-shrinkable polyester films of Examples 2 to 8 and Comparative Examples 1 to 15 are substantially the same as that of Example 1, and the main differences are: the types and amounts of the components, as shown in Tables 1 to 3.
[0046] Table 1
[0047]
[0048]
[0049] Table 2
[0050]
[0051]
[0052] Table 3
[0053]
[0054]
[0055]
[0056] Evaluation Project
[0057] The heat-shrinkable polyester films of Examples 1 to 8 and Comparative Examples 1 to 15 were subjected to the following tests. For the sake of clarity, the test procedures of the following test items are described using the heat-shrinkable polyester film of Example 1 as a representative.
[0058] Intrinsic viscosity (unit: dL / g) measurement: Measured according to ASTM D4603 (2003 edition) standard test method for determining intrinsic viscosity of polyethylene terephthalate using a glass capillary viscometer. 0.25±0.0025 grams of the heat-shrinkable polyester film of Example 1 was added to 25 mL of a solvent component containing 60 wt% of phenol and 40 wt% of 1,1,2,2-tetrachloroethane to form a mixed solution. Then, the mixed solution was heated at 110±10°C for 1 hour, and then cooled to form a sample to be tested. The sample to be tested was measured at 25°C using an Ostwald viscometer, and the intrinsic viscosity was calculated using the Huggins equation.
[0059] Glass transition temperature (Tg, unit: °C) measurement: A differential thermal scanning analyzer (brand: TAInstruments; model: 2910 Modulated DSC) was used to measure the unstretched plate and the heat-shrinkable polyester film of Example 1. The parameter conditions of the measurement were heating from -50°C to 300°C, and the heating rate was 10°C / min to obtain a differential thermal scanning curve. According to the differential thermal scanning curve, the glass transition temperature was obtained.
[0060] 95℃ shrinkage (unit: %) measurement: According to JIS Z1709 standard method (2017 updated version), the heat shrinkable polyester film of Example 1 was cut into a sample with a size of 100mm×100mm. The sample was immersed in 95℃ hot water for 10 seconds to form an immersed sample. Then, the immersed sample was taken out from the hot water and cooled in 30℃ cold water for 30 seconds. Then, the length (L) in the perpendicular machine direction (abbreviated as TD) was measured. TD ) and the length in the machine direction (MD) (L MD ), and calculate the heat shrinkage rate in the perpendicular machine direction and the heat shrinkage rate in the machine direction according to the following formula.
[0061] 95℃TD heat shrinkage (%) = [(100-L TD ) / 100]×100%
[0062] 95℃MD heat shrinkage (%) = [(100-L MD ) / 100]×100%
[0063] Yield strength in the perpendicular machine direction (unit: MPa) measurement: According to ASTM D882 standard method (2018 edition), the heat shrinkable polyester film of Example 1 was cut into test samples with a length of 150 mm in the perpendicular machine direction and a length of 15 mm in the machine direction. The test sample was placed in a tensile testing machine (brand: Guanglei Instrument Co., Ltd.; model: QC-508B1), and two clamps with a distance of 100 mm were used to clamp the two ends of the test sample in the perpendicular machine direction, and the two ends were stretched until the test sample broke, and a strain-stress curve was obtained, and from the strain-stress curve, the yield point when plastic deformation began to occur was obtained, and the corresponding stress was the yield strength.
[0064] Elongation at break (unit: %) and elongation at break variation (unit: %) measurement: According to ASTM D882 standard method (2018 edition), two sheets of heat-shrinkable polyester films of Example 1 were cut into a first test sample and a second test sample with a length of 150 mm in the machine direction and a length of 15 mm in the perpendicular machine direction. Then, a material testing machine (brand: Guanglei Instrument Co., Ltd.; model: QC-508B1) was used to clamp the two ends of the first test sample in the machine direction respectively with two clamps set at a distance of 100 mm, and stretch the two ends until the first test sample broke, and the distance (D0) of the clamps when the first test sample broke was recorded, and the elongation at break E0 of the first test sample was calculated according to the following formula. The second test sample is placed in an oven at a temperature of 60° C. for 1 hour to form an aged film. Then, the above-mentioned measurement process is performed to record the distance (D1) of the clamp when the second test sample breaks, and the elongation at break E1 of the second test sample is calculated according to the following formula.
[0065] Elongation at break (E0, %) = [(D0-100) / 100] × 100%
[0066] Elongation at break (E1, %) = [(D1-100) / 100] × 100%
[0067] Elongation at break variation (%) = |E0-E1|
[0068] Measurement of natural shrinkage (unit: %): The heat-shrinkable polyester film of Example 1 was cut into test samples with a size of 100 mm × 100 mm. The test samples were placed in a constant temperature and humidity oven at 40°C and a relative humidity of 65% for 168 hours to form a treated film. Then, the treated film was taken out of the constant temperature and humidity oven, and the length (L) of the treated film in a perpendicular machine direction (abbreviated as TD) was measured. TD ), and calculate the natural shrinkage in the perpendicular machine direction according to the following formula.
[0069] Natural shrinkage (%) = [(100-L TD ) / 100]×100%
[0070] Average peel strength (unit: gf / mm) measurement: Using a shrink film closing machine (brand: Sanxia), the two ends of the heat shrinkable polyester film of Example 1 in the vertical mechanical direction are overlapped, and at the same time, 1,3-dioxolane (as a closing agent) is applied between the two ends to bond the two ends to form a hollow flat long strip film, and then cut into a hollow cut product with a length of 15 cm in the mechanical direction. Cut at the overlapping part of the two ends of the hollow cut product, and cut out 5 strip-shaped test samples, and each test sample includes two overlapping cut pieces. The size of each test sample is 3 cm in length in the mechanical direction and 20 cm in length in the vertical mechanical direction. Each test sample was placed in a peel strength tester (brand: INSTRON; model: 5566), and at a peel speed of 100 mm / min, a tensile force from small to large was applied to one of the cut pieces of each test sample along a vertical mechanical direction until the cut pieces were separated from each other, and the tensile force at the time of separation was recorded, so as to calculate the peel strength of each test sample and the average peel strength.
[0071] Evaluation of penetration degree: The heat-shrinkable polyester film of Example 1 is introduced into a hand-joining machine (brand: Sanxia), and the two ends of the heat-shrinkable polyester film in the vertical mechanical direction are overlapped by the hand-joining machine. At the same time, 1,3-dioxolane (hand-joining agent) is applied between the two ends to bond the two ends to form a hollow flat long film, and then rolled into a cylindrical roll film. Next, the cylindrical roll film is placed in an environment of 28°C for 30 days, and then a cut piece with a length of 100 cm in the mechanical direction is cut from the inner side of the cylindrical roll film. Then, the length ratio of the hand-joining agent on the surface of the cut piece is measured. If the hand-joining agent accounts for less than 5%, it is represented by ○, and if the hand-joining agent accounts for more than 5%, it is represented by X.
[0072] Table 4
[0073]
[0074]
[0075] Table 5
[0076]
[0077]
[0078] Table 6
[0079]
[0080] It can be seen from the experimental results in Table 1 and Table 4 that by controlling the total amount of the modified alcohol mixture to 18 mol% to 26 mol% and the amount of 2-methyl-1,3-propanediol to 3.5 mol% to 22 mol%, the average peel strength of the heat-shrinkable polyester films of Examples 1 to 8 is 10 gf / mm to 31 gf / mm, the yield strength in the perpendicular mechanical direction is 7.6 MPa to 12.4 MPa, the natural shrinkage is 0.1% to 1.0%, the penetration degree is ○, and the elongation at break variation is 6% to 91%. This means that during the process of the heat-shrinkable polyester film being introduced into the hand-closing machine and forming a hollow flat long film, the two ends of the bond are not easily affected by the external force in the subsequent process and separated from each other, so that it can be stably shrunk and wrapped on the container, and has the advantage of bonding stability. Furthermore, during the process of forming the hollow flat long strip film from the heat-shrinkable polyester film, the sealing agent will not penetrate into the inner surface or outer surface of the hollow flat long strip film, making it less likely that the inner surface or the outer surface will stick together, thereby enabling the sleeve to be produced smoothly.
[0081] In addition, when the heat-shrinkable polyester film cannot be sold or used immediately and is stored, the difference between the elongation of the heat-shrinkable polyester film before and after storage for a period of time is small. Therefore, in the process of forming the hollow flat long film or the sleeve being heat-shrinked and wrapped in the container after storage for a period of time, the heat-shrinkable polyester film can withstand the external tension at a high production speed without breaking. Since there is no problem of breaking, the production will not be stopped or the production speed will not decrease, so that the production capacity per unit time can be maintained, thereby having the advantage of production and processing stability. At the same time, the degree of natural shrinkage of the heat-shrinkable polyester film after storage for a period of time is small, and it has good storage dimensional stability. Therefore, even if the heat-shrinkable polyester film is not used immediately after production, the heat-shrinkable polyester film can still maintain a certain size and meet the needs of the industry.
[0082] In contrast, Comparative Examples 1 to 15. Referring to Tables 2 and 5, in Comparative Example 1, the heat-shrinkable polyester film does not contain neopentyl glycol or 1,4-cyclohexanedimethanol, resulting in a variation of the elongation at break of the heat-shrinkable polyester film of 131%. It can be seen that the heat-shrinkable polyester film obtained under such conditions is not easy to withstand the external tensile force at a high production speed when it is used to make a sleeve or when the sleeve is heat-shrunk and wrapped around a container after being formed after being stored for a period of time, resulting in the problem of easy breakage.
[0083] Referring to Table 2 and Table 5, in Comparative Example 2, the total amount of the modified alcohol mixture of the heat shrinkable polyester film is 29 mol% and the amount of 2-methyl-1,3-propanediol is 25 mol%, resulting in the heat shrinkable polyester film having a variation of elongation at break of 441%, a yield strength in the vertical mechanical direction of 6.9 MPa, a natural shrinkage of 1.4% and a permeability of X. It can be seen that the heat shrinkable polyester film obtained under such conditions is not easy to withstand the external tension at a high production speed when used to make a sleeve or when the sleeve is formed and then wrapped in a container by heat shrinkage after being stored for a period of time, resulting in the problem of easy breakage. In addition, in the process of forming a hollow flat long film, the heat shrinkable polyester film is easy to penetrate into the inner surface or outer surface of the hollow flat long film, resulting in the problem of the inner surface or outer surface being easily bonded together. At the same time, the heat shrinkable polyester film has a large degree of natural shrinkage after being stored for a period of time, and has the problem of poor storage dimensional stability.
[0084] Referring to Table 2 and Table 5, in Comparative Example 3, the heat shrinkable polyester film does not contain neopentyl glycol or 1,4-cyclohexanedimethanol, resulting in a variation of the elongation at break of the heat shrinkable polyester film of 383%, and a natural shrinkage of 2.9%. It can be seen that the heat shrinkable polyester film obtained under such conditions is not easy to withstand the external tension at a high production speed when used to make a sleeve or when the sleeve is formed and then wrapped in a container by heat shrinkage after being stored for a period of time, resulting in the problem of easy breakage. At the same time, the heat shrinkable polyester film has a large degree of natural shrinkage after being stored for a period of time, and has the problem of poor storage dimensional stability.
[0085] Referring to Table 2 and Table 5, in Comparative Examples 4 to 7, the total amount of the modified alcohol mixture of the heat-shrinkable polyester film is 28 mol%, 38 mol%, 33.1 mol% and 33.8 mol%, respectively, resulting in the elongation at break of the heat-shrinkable polyester film being 177%, 180%, 275% and 306%, respectively, and the yield strength in the vertical mechanical direction being 6.9 MPa, 6.4 MPa, 6.8 MPa and 6.7 MPa, respectively, and the penetration degree is X. It can be seen that the heat-shrinkable polyester film obtained under such conditions is not easy to withstand the external tension at a high production speed after being stored for a period of time and used to make a sleeve or to wrap the sleeve in a container by heat shrinkage after forming the sleeve, resulting in the problem of easy breakage. In addition, in the process of forming the hollow flat long strip film of the heat-shrinkable polyester film, the palm-jointing agent easily penetrates into the inner surface or outer surface of the hollow flat long strip film, resulting in the problem of the inner surface or outer surface being easily bonded together. In addition, in Comparative Examples 5 to 7, in addition to the above problems, the natural shrinkage rates of the heat-shrinkable polyester film are 3.8%, 3.0% and 3.3%, respectively, which means that the heat-shrinkable polyester film has a large degree of natural shrinkage after being stored for a period of time, and has a problem of poor storage dimensional stability. Comparative Example 5 is equivalent to the raw material composition for forming copolyester disclosed in PCT International Application Publication No. WO2022072477, and it can be seen from the above that the heat-shrinkable film of the PCT International Application Publication does have problems of breakage, adhesion and poor storage dimensional stability, and cannot meet the requirements of the present invention.
[0086] Referring to Table 3 and Table 6, in Comparative Example 8, the total amount of the modified alcohol mixture of the heat shrinkable polyester film is 32 mol%, does not contain neopentyl glycol or 1,4-cyclohexanedimethanol, and the amount of 2-methyl-1,3-propanediol is 24 mol%, resulting in the yield strength of the heat shrinkable polyester film in the vertical mechanical direction being 6.9 MPa, the natural shrinkage rate being 3.7%, and the penetration degree being X. It can be seen that in the process of forming a hollow flat long film, the heat shrinkable polyester film obtained under such conditions, the palm-jointing agent easily penetrates into the inner surface or outer surface of the hollow flat long film, resulting in the problem of the inner surface or outer surface being easily bonded together. In addition, the heat shrinkable polyester film has a large degree of natural shrinkage after being stored for a period of time, and has the problem of poor storage dimensional stability.
[0087] Referring to Table 3 and Table 6, in Comparative Example 9, the total amount of the modified alcohol mixture of the heat-shrinkable polyester film is 34 mol%, does not contain neopentyl glycol or 1,4-cyclohexanedimethanol, and the amount of 2-methyl-1,3-propanediol is 24 mol%, resulting in the heat-shrinkable polyester film having a variation of elongation at break of 145%, a yield strength in a perpendicular mechanical direction of 6.2 MPa, a natural shrinkage of 4.0%, and a permeability of X. It can be seen that the heat-shrinkable polyester film obtained under such conditions is not easy to withstand the external tension at a high production speed when used to make a sleeve or when the sleeve is formed and then wrapped in a container by heat shrinkage after being stored for a period of time, resulting in the problem of easy breakage. In addition, in the process of forming a hollow flat long strip film of the heat-shrinkable polyester film, the palm-jointing agent easily penetrates into the inner surface or outer surface of the hollow flat long strip film, resulting in the problem of the inner surface or outer surface being easily bonded together. In addition, the heat-shrinkable polyester film has a large degree of natural shrinkage after being stored for a period of time, and has the problem of poor storage dimensional stability.
[0088] Referring to Table 3 and Table 6, in Comparative Example 10, the total amount of the modified alcohol mixture of the heat-shrinkable polyester film is 17.5 mol%, resulting in the heat-shrinkable polyester film having a yield strength of 13.4 MPa and an average peel strength of 4 gf / mm in the perpendicular mechanical direction. It can be seen that during the process of forming the hollow flat long strip film, or even after the heat-shrinkable polyester film is wrapped in the container, the two bonded ends are easily affected by external forces in the subsequent process and separated from each other. Therefore, the heat-shrinkable polyester film has poor bonding stability.
[0089] Referring to Table 3 and Table 6, in Comparative Example 11, the total amount of the modified alcohol mixture of the heat-shrinkable polyester film is 26.5 mol%, resulting in a yield strength of 6.4 MPa and a permeability of X in the perpendicular mechanical direction of the heat-shrinkable polyester film. It can be seen that during the process of forming the hollow flat long strip film of the heat-shrinkable polyester film, the bonding agent easily penetrates into the inner surface or outer surface of the hollow flat long strip film, resulting in the problem of the inner surface or the outer surface being easily bonded together.
[0090] Referring to Table 3 and Table 6, in Comparative Example 12, the total amount of the modified alcohol mixture of the heat-shrinkable polyester film is 26.5 mol% and the amount of 2-methyl-1,3-propanediol is 22.5 mol%, resulting in a variation of the elongation at break of the heat-shrinkable polyester film of 305%, a yield strength in the vertical mechanical direction of 6.8 MPa and a permeability of X. It can be seen that the heat-shrinkable polyester film obtained under such conditions is not easy to withstand the external tension at a high production speed when used to make a sleeve or when the sleeve is formed and then wrapped in a container by heat shrinkage after being stored for a period of time, resulting in the problem of easy breakage. In addition, in the process of forming the heat-shrinkable polyester film into a hollow flat long film, the palm-jointing agent easily penetrates into the inner surface or outer surface of the hollow flat long film, resulting in the problem of the inner surface or outer surface being easily bonded together.
[0091] Referring to Table 3 and Table 6, in Comparative Example 13, the amount of 2-methyl-1,3-propanediol in the heat-shrinkable polyester film is 22.5 mol%, resulting in a variation of the elongation at break of the heat-shrinkable polyester film of 388% and a yield strength of 7.1 MPa in the perpendicular mechanical direction. It can be seen that the heat-shrinkable polyester film obtained under such conditions is not easy to withstand the external tension at a high production speed after being stored for a period of time and is used to make a sleeve or to wrap the sleeve in a container by heat shrinkage after forming the sleeve, resulting in the problem of easy breakage.
[0092] Referring to Table 3 and Table 6, in Comparative Example 14, the total amount of the modified alcohol mixture of the heat shrinkable polyester film is 17.5 mol%, resulting in the yield strength of the heat shrinkable polyester film in the perpendicular mechanical direction being 13.8 MPa, the average peel strength being 2 gf / mm, and the elongation at break variation being 341%. It can be seen that in the process of forming the hollow flat long strip film, or even after being heat-shrinked and wrapped in the container, the two ends of the heat shrinkable polyester film are easily separated from each other by the external force in the subsequent process, so the bonding stability of the heat shrinkable polyester film is not good. Furthermore, after the heat shrinkable polyester film obtained under such conditions is stored for a period of time, it is not easy to withstand the external tension at a high production speed when used to make a sleeve or when the sleeve is heat-shrinked and wrapped in a container after being formed, resulting in the problem of easy breakage.
[0093] Referring to Table 3 and Table 6, in Comparative Example 15, the total amount of the modified alcohol mixture of the heat-shrinkable polyester film is 26.5 mol%, resulting in a variation of the elongation at break of the heat-shrinkable polyester film of 364%, a yield strength of 6.2 MPa in the perpendicular mechanical direction, and a permeability of X. It can be seen that the heat-shrinkable polyester film obtained under such conditions is not easy to withstand the external tension at a high production speed when used to make a sleeve or when the sleeve is formed and then wrapped in a container by heat shrinkage after being stored for a period of time, resulting in the problem of easy breakage. In addition, in the process of forming the heat-shrinkable polyester film into a hollow flat long strip film, the palm-jointing agent easily penetrates into the inner surface or outer surface of the hollow flat long strip film, resulting in the problem of the inner surface or outer surface being easily bonded together.
[0094] In summary, during the process of the heat shrinkable polyester film being introduced into the closing machine and forming a hollow flat long film, the two ends of the bonding are not easily separated from each other by the external force in the subsequent process, and the closing agent will not penetrate into the inner surface or outer surface of the hollow flat long film, so that the problem of the inner surface or the outer surface being bonded together is not easy to occur, so that the sleeve can be smoothly produced. In addition, the difference between the elongation of the heat shrinkable polyester film before and after being stored for a period of time is small. Therefore, after the heat shrinkable polyester film is stored for a period of time, it is used to make a sleeve or the sleeve is formed and then wrapped in a container by heat shrinkage. The heat shrinkable polyester film is not easy to break due to external tension at a high production speed, so that the production capacity can be maintained per unit time. At the same time, the degree of natural shrinkage of the heat shrinkable polyester film after being stored for a period of time is small, and it has good storage dimensional stability. Therefore, even if the heat shrinkable polyester film is not used immediately after production, the heat shrinkable polyester film can still maintain a certain size, so the purpose of the present invention can be achieved.
Claims
1. A heat shrinkable polyester film, characterized in that: The heat shrinkable polyester film comprises a polyester formed by a dicarboxyl component and a diol component, wherein the dicarboxyl component comprises at least one of terephthalic acid and dimethyl terephthalate, the diol component comprises ethylene glycol and a modified alcohol mixture, the modified alcohol mixture comprises a first modified alcohol and a second modified alcohol, the first modified alcohol is 2-methyl-1,3-propanediol, the second modified alcohol is selected from neopentyl glycol, 1,4-cyclohexanedimethanol or a combination thereof, and the total amount of the diol component is 100 mol %, the total amount of the ethylene glycol is 74 mol % to 82 mol%, the total amount of the modified alcohol mixture is 18 mol% to 26 mol%, and the amount of 2-methyl-1,3-propanediol is 3.5 mol% to 22 mol%; and the heat-shrinkable polyester film satisfies the following (a) to (c), (a) after being immersed in hot water at 95°C for 10 seconds, the heat shrinkage in the perpendicular machine direction is greater than 48%; (b) after being immersed in hot water at 95°C for 10 seconds, the heat shrinkage in the machine direction is less than 5%; and (c) has an intrinsic viscosity greater than 0.50 dL / g.
2. The heat-shrinkable polyester film according to claim 1, characterized in that: The heat-shrinkable polyester film has a natural shrinkage rate of no more than 1%, and the natural shrinkage rate is [(A0-A1) / A0]×100%, A0 and A1 respectively represent the length of the heat-shrinkable polyester film in one direction before and after treatment, and the treatment temperature is 40°C, the relative humidity is 65% and the time is 168 hours.
3. The heat-shrinkable polyester film according to claim 1, characterized in that: The heat shrinkable polyester film has a variation of elongation at break of less than 100%, and the variation of elongation at break is the absolute value of the difference between the elongation at break of the heat shrinkable polyester film before and after aging treatment, and the aging treatment temperature is 60° C. and the time is 1 hour.
4. The heat-shrinkable polyester film according to claim 1, characterized in that: The heat-shrinkable polyester film has a yield strength of 7.5 MPa to 13 MPa in a perpendicular machine direction.
5. The heat-shrinkable polyester film according to claim 1, characterized in that: Based on 100 mol% of the total amount of the diol component, the total amount of the second upgraded alcohol is 4 mol% to 22 mol%.
6. The heat-shrinkable polyester film according to claim 1, characterized in that: Based on 100 mol% of the total amount of the diol component, the total amount of the second upgraded alcohol is 4 mol% to 17 mol%.
7. The heat-shrinkable polyester film according to claim 1, characterized in that: The amount of the 2-methyl-1,3-propanediol is 3.5 mol% to 20 mol% based on 100 mol% of the total amount of the diol component.
8. The heat-shrinkable polyester film according to claim 1, characterized in that: Based on 100 mol% of the total amount of the diol component, the total amount of the modified alcohol mixture is 21 mol% to 25 mol%, and the amount of the 2-methyl-1,3-propanediol is 17 mol% to 20 mol%.
9. The heat-shrinkable polyester film according to claim 1, characterized in that: The diol component also includes bis(2-hydroxyethyl)terephthalate.
10. The heat-shrinkable polyester film according to claim 1, characterized in that: The diol component does not include polyglycols.
Citation Information
Patent Citations
Heat-shrinkable pet film and method for making the same
US20080057237A1
Propane diol-based polyester resin and shrink film
US7008698B2
Heat shrinkable films, and method of manufacturing the same
WO2022072477A1
Shrinkable polyester films
WO2022076763A1